Comparing wavelengths simulated by the coastal wave model CWAM and TerraSAR-X satellite data. (July 2016) - Gebhardt, Claus; Pleskachevsky, Andrey; Rosenthal, Wolfgang; Lehner, Susanne; Hoffmann, Peter; Kieser, Jens; Bruns, Thomas
Highlights: The forecast quality of the high resolution coastal wave model CWAM is validated. Recent sea state data are compared between CWAM and the TerraSAR-X satellite. Potential wave modelling errors are discussed. Abstract: The accuracy of the high resolution coastal wave forecast model CWAM is validated on the basis of sea state information from satellite images of TerraSAR-X (TS-X). At the same time, the performance of the satellite retrieval of sea state parameters is demonstrated. Employing 2-dimensional spatial Fourier Transformation, image spectra are derived from TS-X and locally varying patterns of the peak wavelength are provided using state-of-the-art satellite retrieval. Subsequently, wavelength comparisons are performed between a typical set of TS-X scenes acquired in December 2013 over the German Bight and the model hindcasts. The results are mostly in reasonable agreement. Potential shortcomings of the wave model are discussed as well.